1978
DOI: 10.1073/pnas.75.11.5311
|View full text |Cite
|
Sign up to set email alerts
|

A major serine protease in rat skeletal muscle: Evidence for its mast cell origin

Abstract: The physical, chemical, and immunologic properties of a protease from rat skeletal muscle, proposed to function in the degradation of certain intracellular enzymes, are identical to those of a chymotrypsin-like serine protease isolated from peritoneal mast cells. The results of polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate and 8 M urea indicate that the two rat proteases have identical mobilities corresponding to a molecular weight of 26,000. The relative amino acid compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The amino acid composition (table 1) of this enzyme is clearly different from that of the atypical mast cell protease, but it is remarkably similar to that of the skeletal muscle protease [28]. The amino-terminal sequences of the mast cell protease and the skeletal muscle protease are identical for the first 35 residues [28].…”
Section: Purificationmentioning
confidence: 88%
See 2 more Smart Citations
“…The amino acid composition (table 1) of this enzyme is clearly different from that of the atypical mast cell protease, but it is remarkably similar to that of the skeletal muscle protease [28]. The amino-terminal sequences of the mast cell protease and the skeletal muscle protease are identical for the first 35 residues [28].…”
Section: Purificationmentioning
confidence: 88%
“…The amino-terminal sequences of the mast cell protease and the skeletal muscle protease are identical for the first 35 residues [28]. Immunodiffusion tests for cross-reactivity using anti-rat mast cell protease indicated that the mast cell and skeletal muscle proteases are immunologically identical [28]. Finally, immunofluorescent localization of skeletal muscle protease showed that this enzyme was in fact derived from mast cells present in the connective tissue of muscle (N. Katunuma, personal communication).…”
Section: Purificationmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the presence of cytochrome c oxidase in the high density fraction containing the proteinase-carboxypeptidase activities strongly suggested an inner mitochondrial membr~e location. It was dif~cult, however, to explain the high density of the material (P = 1.25 g/ cm3) which sedimented through the layer of 1.7 M sucrose compared to an average density of 1.20 g/cm3 measured for mitochondria [ 161. We have speculated that the high density proteinase represents the 'tight junction' within mitochondria, sites, where inner and outer membrane are in close proximity [ 11. A reevaluation of the localization of the serine proteinase and carboxypeptidase was initiated by the demonstration [8,9] that the 'group-specific enzymes' [5] isolated from rat small intestine and skeletal muscle were of mast cell origin. Since it is not generally known that rat liver contains mast cells, it was necessary to demonstrate their presence in liver ( fig.1).…”
Section: Discdonmentioning
confidence: 99%
“…The proteinase in the inner membrane of mitochondria has also been localized [6,7]. Recent experiments [8,9] have shown that the group specific proteinases isolated from small intestine [8] and from skeletal muscle [9] are of mast cell origin. In the light of these findings it became important to examine this possibility, although mast cells have not been described as an integral part of the liver [lo].…”
Section: Introductionmentioning
confidence: 99%